2022
DOI: 10.3390/w14091504
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Characterization of the Annual Maximum Daily Precipitation in the Southwestern Iberian Peninsula (1851–2021)

Abstract: High-intensity rainfall can raise fluvial channel levels, increasing the risk of flooding. Maximum precipitation depths are used to estimate return periods and, thus, calculate the risk of this type of event. To improve these estimates in Southwest Europe, we studied the behavior of extreme rainfall using the historical records of San Fernando (Cádiz, southwest Spain), obtaining the maximum daily annual rainfall (period 1851–2021). Local risk levels for intense precipitation were established based on the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…An analysis of the synoptic situations behind two extremely catastrophic rainfall events and their environmental effects is presented. The use of such a uniquely long series of precipitation maxima in an urban area has the potential to provide a better insight into their variability, which can be utilised in forecasting them [6,12]. Precipitation, unlike air temperature, does not show statistically significant long-term changes, but instead demonstrates short-term fluctuations, including periodic ones [7,8,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the synoptic situations behind two extremely catastrophic rainfall events and their environmental effects is presented. The use of such a uniquely long series of precipitation maxima in an urban area has the potential to provide a better insight into their variability, which can be utilised in forecasting them [6,12]. Precipitation, unlike air temperature, does not show statistically significant long-term changes, but instead demonstrates short-term fluctuations, including periodic ones [7,8,13].…”
Section: Introductionmentioning
confidence: 99%
“…For Europe, such an analysis was carried out by Madsen et al [22], who found a general increase in the volume of extreme precipitation, though without any marked tendencies in the increase in maximum flows. However, few of these studies are based on secular, series of measurements of over 100 years [12].…”
Section: Introductionmentioning
confidence: 99%
“…Проблеме подбора закона распределения, адекватно описывающего статистику МССО, посвящено большое количество исследований [8][9][10][11][12][13][14][15][16][17]. Применение классических методов моделирования ММСО, использующих асимптотическое распределение экстремальных значений, подробно проанализировано в обзоре [11].…”
Section: Introductionunclassified